2011
DOI: 10.1007/s10484-011-9157-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Event-Related Potentials Elicited by Conceptual Mismatch Between Expectations and Self-chosen TV Images

Abstract: When a voluntary action is followed by an unexpected stimulus, a late positive potential (LPP) with a posterior scalp distribution is elicited in a latency range of 500-700 ms. In the present study, we examined what type of mismatch between expectations and action outcomes was reflected by the LPP. Twelve student volunteers participated in a task simulating choice of TV programs. After choosing one of three options displayed as a cue stimulus, they viewed a second stimulus (still TV image). To manipulate the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The LPP component is generally elicited by a difference between an expectation and the subsequent feedback. In additional research (Adachi, Morikawa, & Nittono, 2011), we also confirmed that the LPP component is observed when the initial stimulus is a letter and the feedback occurs in the form of an image.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The LPP component is generally elicited by a difference between an expectation and the subsequent feedback. In additional research (Adachi, Morikawa, & Nittono, 2011), we also confirmed that the LPP component is observed when the initial stimulus is a letter and the feedback occurs in the form of an image.…”
Section: Discussionsupporting
confidence: 76%
“…The present authors have examined the physiological phenomena that result when a participant identifies a mismatch between an initial signal and a subsequent feedback signal (Adachi, Morikawa, & Nittono, 2007, 2011. A specific ERP component occurring around 600 ms and called the late positive potential (LPP) is elicited when a mismatch is detected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent to the enhanced P3a, within-group analyses indicated that the healthy control group had an amplified posteriorly distributed LPP (660-700 msec) to unexpected action outcomes. Studies by Nittono et al suggest that the mismatch between the expected and actual action outcome is also reflected in the LPP, but at a higher, conceptual level of mismatch than the preceding mismatch indices (Adachi et al, 2007;Adachi, Morikawa, & Nittono, 2011;Iwanaga & Nittono, 2010). Debate continues over what composite cognitive processes generate positive slow waves during this late stage of outcome processing.…”
Section: Electrophysiological Resultsmentioning
confidence: 99%
“…This pattern was noted in all experiments, suggesting that expectancy mechanisms interact with timing in the same way irrespective of the magnitude or nature of the manipulations. Studies using event-related potentials (ERPs), which is an electrophysiological index of brain processes with high temporal resolution, suggest that unpredicted sensory outcomes of voluntary actions are processed as deviant events (Waszak & Herwig, 2007;Nittono & Ullsperger, 2000;Nittono, 2006;Heinks-Maldonado et al, 2005;Adachi, Morikawa & Nittono, 2011). Unpredictable stimuli may also be viewed as distractors, given that unexpected events comprise an involuntary attention shift from the task-relevant information (in this case, timing) to nontemporal information.…”
Section: Overview Of Experimental Findingsmentioning
confidence: 99%